The communal and renewed kibbutz: ideology, management and institutional change - Sofer, Michael; Grossman, Ephraim S.; Grossman, David (IGiPZ PAN, 2015)
This study considers the roles of management and ideology in modifying the sustainability of communal systems. We approached this issue by discussing the major forces that shaped the planned kibbutz and the recent processes that have brought about its current transformation. Using a questionnaire-based survey we tried to reveal the relative importance that the members attach to traditional kibbutz values and their perception of the tension between the original ideology and the management strategies that have been imposed on the communal society by both external and internal forces. The findings indicate that pragmatism tends to prevail over ideology and communality has difficulty in functioning effectively in a highly complex and changing world. It points to the weakening of the communal system and to growing disengagement from principles of equality. However, the process and project of reshaping the kibbutz is ongoing.
24 cm
Keywords: Israel; kibbutz; communality; renewed kibbutz; organizational changes; restructuring